A study on the zakat and infaq or sodaqoh accounting application under SFAS 109 in Al-Falah Social Fund Foundation (YDSF) Surabaya - Siti Wasila; Nanang Shonhadji (STIE Perbanas Surabaya, 2014)
This study aims to evaluate the reporting and the application of zakat accounting and its effectiveness under the Statements of Financial Accounting Standard (SFAS) No. 109 in Al-Falah Social Fund Foundation (YDSF) Surabaya. This study used the method of primary and secondary data. The primary data were obtained through indepth interviews regarding the accounting and financial reporting of the foundation. The result shows that the accounting which is based on Islamic Syariah has a great impact on the humanitarian aspects of the accounting of zakat and infaq or sodaqoh. Thus, the accounting of zakat and infaq or sodaqoh stimulates the individual behavior across the environment to be always transformational. The accountability established within the organization includes physical, moral and spiritual aspects. The physical aspect of this research is the financial statements while the moral and spiritual aspectsare the realization of organizational accountability to God by trying to run its activities based on syariah. For further studies, the researchers should not only focus on one basic course, but also on the basis of social funds in Al-Falah foundation Surabaya as the house of sodaqoh, wallet for the poor, etc. that has also adopted SFAS No. 109 in its financial statements. Beside, the information should be in the long term in order to get effective and efficient information for a better result.